Evaluation of a Microencapsulated Form of Zinc Oxide on Weanling Pig Growth Performance, Intestinal Morphology, and Zinc Excretion - Payton L. Dahmer; Franco S. Matias-Ferreyra; Cassandra K. Jones (Kansas Agricultural Experiment Station Research Reports, 2023)
A total of 350 pigs (DNA 200 × 400; initially 13.31 ± 0.04 lb BW) were used in a 42-d study with 5 pigs per pen and 12 pens per treatment. At weaning, pigs were randomly allocated to pens and pens were randomly allotted to dietary treatments. Dietary treatments were: 1) negative control (standard nursery diet containing 110 ppm Zn from trace mineral premix); 2) control diet with 3,000 ppm added Zn in the form of ZnO in phase 1 and 2,000 ppm added Zn in the form of ZnO in phase 2 (High-ZnO); 3) control diet with 400 ppm added Zn in the form of ZnO in phases 1 and 2 (Low-ZnO); 4) 3,000 ppm added Zn in the form of microencapsulated ZnO in phase 1 and 2,000 ppm added Zn in the form of microencapsulated ZnO in phase 2 (High-MZnO); and 5) 400 ppm added Zn in the form of microencapsulated ZnO in phases 1 and 2 (Low-MZnO). Pigs were weighed and feed disappearance was determined to evaluate ADG, ADFI, and F/G. On d 10 and d 28, fecal samples from 3 pigs per pen were collected for fecal Zn concentrations. On d 28, 30 pigs (6 pigs per treatment) were euthanized, and small intestinal tissue was collected to evaluate morphology. There was no evidence of differences in ADG, ADFI, or F/G for the entire treatment period (d 0 to d 28;P>0.05). During the common phase 3 (d 28 to 42) pigs fed the negative control, High-MZnO, or Low-MZnO had improved (P<0.0001) ADG compared to pigs fed High- or Low-ZnO, which was driven by an increase in ADFI (P<0.0001). For the entire experiment (d 0 to 42), pigs fed Low-ZnO or High-ZnO had reduced (P<0.0001) ADG compared those fed the negative control. There was no evidence that small intestinal morphology differed significantly between treatments (P>0.05). Finally, a significant treatment × day interaction (P= 0.04) was observed for fecal Zn concentrations, where pigs fed High-ZnO had greater fecal Zn levels on d 10 and d 28 compared to pigs fed all other treatments.
Keywords: weanling pig; growth; zinc oxide; zinc alternative